Evapotranspiration from Spider and Jade Plants Can Improve Relative Humidity in an Interior Environment - Kerschen, Eric W.; Garten, Caleb; Williams, Kimberly A.; Derby, Melanie M. (My University, 2016)
Plants in the interiorscape have many documented benefits, but their potential for use in conjunction with mechanical heating, ventilation, and air conditioning (HVAC) systems to humidify dry indoor environments requires more study. In this research, evaporation and evapotranspiration rates for a root medium control, variegated spider plants (Chlorophytum comosum), and green jade plants (Crassula argentea) were measured over 24 hours at 25% and 60% relative humidity (RH) and 20 °C to generate data for calculation of the leaf surface area and number of plants necessary to influence indoor humidity levels. Evaporation and evapotranspiration rates were higher for all cases at 25% RH compared with 60% RH. At 25% RH during lighted periods, evapotranspiration rates were ?15 g·h?1 for spider plants and 8 g·h?1 for jade plants. Spider plants transpired during lighted periods due to their C3 photosynthetic pathway, whereas jade plants had greater evapotranspiration rates during dark periods—about 11 g·h?1—due to their crassulacean acid metabolism (CAM) photosynthetic pathway. A combination of plants with different photosynthetic pathways (i.e., C3 and CAM combination) could contribute to greater consistency between evapotranspiration rates from day to night for humidification of interior spaces. Using the measured data, calculations indicated that 32,300 cm2 total spider plant leaf surface area, which is 25 spider plants in 4-inch-diameter pots or fewer, larger plants, could increase the humidity of an interior bedroom from 20% RH to a more comfortable 30% RH under bright interior light conditions.
Citation: Kerschen, E., Garten, C., Williams, K., & Derby, M. (2016). Evapotranspiration from Spider and Jade Plants Can Improve Relative Humidity in an Interior Environment. HortTechnology, 26(6), 803-810. doi: 10.21273/HORTTECH03473-16
Keywords: Chlorophytum; Crassula; Interiorscape; Passive Humidification; Transpiration